Role of MAPK‐mediated endoplasmic reticulum stress signaling in the heart during aging in senescence‐accelerated prone mice. (18th April 2016) - Sreedhar, Remya; Giridharan, Vijayasree V.; Arumugam, Somasundaram; Karuppagounder, Vengadeshprabhu; Palaniyandi, Suresh S.; Krishnamurthy, Prasanna; Quevedo, Joao; Watanabe, Kenichi; Konishi, Tetsuya; Thandavarayan, Rajarajan A.
Abstract: Heart failure is typically related to aging as there is a definite relationship between age‐related changes in the heart and the pathogenesis of heart failure. We have previously reported the involvement of p38 mitogen‐activated protein kinase protein in cardiac function using animal models of heart failure. To further understand its relationship with aging‐induced heart failure, we have compared its expression in the hearts of senescence accelerated‐prone (SAMP8) mice and their control (SAMR1) with normal aging behavior. We have identified its activation along with reduced expression of 14‐3‐3η protein in SAMP8 mice hearts than in SAMR1 mice. To reveal the downstream signaling, we have measured the endoplasmic reticulum stress marker proteins along with some inflammatory and apoptosis markers and identified a significant increase in SAMP8 mice hearts than that of SAMR1. In addition, we have performed comet assay and revealed a significant DNA damage in the cardiomyocytes of SAMP8 mice when compared with SAMR1 mice. All these results demonstrate the role of 14‐3‐3η protein and the downstream mitogen‐activated protein kinase‐mediated endoplasmic reticulum stress, and apoptosis and DNA damage in aging‐induced cardiac malfunction in SAMP8 mice. Thus targeting this signaling might be effective in treating age‐related cardiac dysfunction. © 2016 BioFactors, 42(4):368–375, 2016